Lipid oxidation and antimicrobial activity of cooked beef patties as influenced by leaf extracts of “Cemba” (Albizia lebbeckoides [DC.] Benth) - Hajrawati Hajrawati; Henny Nuraini; Irma Isnafia Arief; Dondin Sajuthi (Faculty of Animal Science, Universitas Gadjah Mada, 2019)
Cemba (Albizia lebbeckoides [DC.] Benth.) leaf extract (CLE) was evaluated for some physical properties, antioxidant and antimicrobial activities incorporated into beef patties during cold storage. Four Formulation employed were control, butylated hydroxytoluene (BHT) 0.01, CLE 0.5, and CLE 1% (w/w). The variables measured were proximate composition, cooking parameters, pH, aw, WHC, color, total phenolic content, antioxidant capacity, DPPH scavenging activity, TBARS value, and microbial total. The data were analyzed using ANOVA one factor for proximate and cooking parameters, and ANOVA with factorial 4x5 for pH, aw, WHC, color, total phenolic content, antioxidant capacity, DPPH scavenging activity, TBARS value, and microbial total and continued with Tukey test. The results of the study showed that the addition of the CLE did not affect the proximate composition and cooking parameters of the patties. The cooked beef patties with 1% CLE showed significantly lower (P<0.05) for TBARS value, pH, bacterial total (mesophilic and psychrophilic) compared to 0.5% CLE and controls. The total phenolic content, antioxidant capacity, scavenging activity of CLE 1 % were significantly higher (P<0.05) than 0.5% CLE and controls during the cold storage period (0, 7, 14, 21, and 28 days). Addition of both 0.5 and 1% CLE in cooked beef patty reduced bacteria total. The addition of 1% CLE had equivalent to BHT 0.01% effect in retarding lipid oxidation. In conclusion, the CLE 1% was effective to retard lipid oxidation and inhibit bacteria growth of cooked beef patties.